Health Education Regarding Gerd in Students of Widuri Vocational School, Lebak Bulus, South Jakarta - Sinaga, Wanto; Artharini, Moody (PROMOTOR, 2025)
GERD is a condition where stomach acid rises back into the esophagus, causing a burning sensation in the chest, which occurs when the lower esophageal ring muscle does not close properly causing stomach acid to flow back into the esophagus. PKM was carried out in the Widuri Lebak Bulus Vocational School classroom, with 35 participants which began with a presentation covering: the meaning of GERD, causes, symptoms, as well as appropriate prevention and treatment methods. The participants were given leaflets about GERD, as well as a demonstration of relaxation techniques, ending with a discussion. Activity results based on data distribution from highest to lowest include: a). Gender distribution; GERD is experienced by many women b). Symptoms frequently experienced: 1) Nausea after eating (28.5%), 2). HeartBurn (23 %), 3). Rising food or stomach acid into the mouth (17.2%). 4). People often burp (14.3%). 5). Bad Breath (8.5 %). c) Distribution of causes of GERD: 1) consumption of spicy food by 15 people (43%), 2). Obesity was 10 people (28.5%), 3) Active smokers were 5 people (14.3%), 4). Eat large portions as many as 3 people (8.5%), 5). 2 people (5.7%) consumed fizzy foods. The assessment method uses Pre-Test & Post-Test at the beginning and end of the activity. Based on the results of the pre-test and post-test, it shows that participants can receive knowledge about GERD, and apply relaxation techniques, with a percentage of 100%. Through PKM, it is hoped that young students can apply the knowledge gained to prevent and manage GERD symptoms well.